Sensing the quantum behaviour of magnetic nanoparticles by electron magnetic resonance. Issue 5 (11th January 2016) - Fittipaldi, M.; Mercatelli, R.; Sottini, S.; Ceci, P.; Falvo, E.; Gatteschi, D.
Abstract : Magnetic nanoparticles: quantum behaviour sensed by EMR. Abstract : We have investigated Magnetic Nanoparticles (MNPs) of spinel type iron oxide (of approximately 8 nm) mineralized in the internal cavity of the bioreactor ferritin nanocage. In particular, we have used Electron Magnetic Resonance, EMR, spectroscopy and taken advantage of the capacity of the protein shells to control the size of the MNPs. EMR measurements in perpendicular and parallel configurations have been recorded at various temperatures. A model based on the giant spin is used to interpret the experimental results. The analysis indicates that the observed quantum behaviour has to be ascribed to the whole MNP and that the thermal population of excited spin states has a strong influence in the EMR behaviour of MNPs.